O compliance no Brasil: a empresa entre a ética e o lucro - Bragato, Adelita Aparecida Podadera Bechelani (2017)
Globalization brought with it positive and negative effects and, among the negative effects, it was possible to observe the companies' search for profit at any cost, even if, for that, there was violation of labor rights, environmental impacts, discrimination, unfair competition, misleading advertising , etc. However, in recent years, a paradigm shift has begun to emerge, both from consumers and stakeholders, who are increasingly looking for ethical, transparent and accountable products and companies.This paradigm shift forced companies to change their profile and reinvent themselves, otherwise it would lose its reputation, a very important factor for business sustainability. It is irrefutable that companies seek the profit necessary for their maintenance, however, this can no longer be the main factor, that is, companies should also observe ethical standards, transparency, social responsibility in order to comply with praise The corporate social function. Thus, the problem that the research faces is whether compliance would be the appropriate tool for the company to fulfill its social function without losing the much needed profit for its maintenance. So, in order to respond to the present questioning, the research, through the hypothetical-deductive method, seeks to address the emergence of the company, as well as the forms of companies accepted by Brazilian law. Subsequently, it seeks to analyze ethics, transparency, social responsibility as forms of corporate sustainability, and, finally, to enter the subject of compliance, object of this work. In response to the problem, it is understood that compliance will allow the company to trace a successful trajectory with ethics and transparency.